2000
DOI: 10.1074/jbc.275.12.8970
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Film Expresses a Complex, Macromolecular Binding Site for Streptococcus sanguis

Abstract: Teeth in the oral cavity are coated with a salivary film or pellicle, which lacks apparent intermolecular organization. This heterogeneous film facilitates binding of early commensal colonizing bacteria, including Streptococcus sanguis. To test the hypothesis that sufficient intermolecular organization exists in salivary films to form binding sites for S. sanguis, an in vitro model of saliva-coated teeth was probed with murine anti-idiotypical monoclonal antibodies (mAb2, anti-ids). The anti-ids were harvested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…The pellicle on tooth enamel and restorative materials is formed by a selective adsorption of salivary macromolecules. In this light, the physicochemical properties of a material influences microbial adhesion either directly or through adsorption of salivary proteins 19,20) .…”
Section: Discussionmentioning
confidence: 99%
“…The pellicle on tooth enamel and restorative materials is formed by a selective adsorption of salivary macromolecules. In this light, the physicochemical properties of a material influences microbial adhesion either directly or through adsorption of salivary proteins 19,20) .…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion assay described by Gong et al (11) was modified to study biofilm formation by using the IVET library for S. gordonii. An overnight culture of the S. gordonii V288 reporter gene (amy-cat) fusion library in THB with TET was diluted 1,000-fold in FMC medium.…”
Section: Methodsmentioning
confidence: 99%
“…S. sanguinis binds directly to saliva-coated teeth, probably by a variety of mechanisms (46). Studies employing saliva-coated hydroxyapatite as a tooth model have revealed both lectin-carbohydrate and nonlectin interactions (27,38,42,64). Some of the salivary components to which S. sanguinis binds have been identified, including salivary immunoglobulin A and ␣-amylase (27).…”
mentioning
confidence: 99%
“…Studies employing saliva-coated hydroxyapatite as a tooth model have revealed both lectin-carbohydrate and nonlectin interactions (27,38,42,64). Some of the salivary components to which S. sanguinis binds have been identified, including salivary immunoglobulin A and ␣-amylase (27). Once bound, S. sanguinis serves as a tether for the attachment of other oral microorganisms that colonize the tooth surface, form dental plaque, and contribute to development of caries and periodontal disease (46).…”
mentioning
confidence: 99%